Acute viral hepatitis in children: a prospective hospital based study - Sharma, Chandra Madhur; Gupta, Sanjay; Aggarwal, Bindu; Chaudhary, Piyush (International Journal of Contemporary Pediatrics, 2020)
Background: Viral hepatitis is a major public health issue throughout the world affecting millions of children despite the availability of vaccines, prophylactic measures and improved sanitation. The objective of the study was to analyze the etiology, clinical features, laboratory parameters and sonological findings of Acute Viral Hepatitis in pediatric population. Methods: A total of 88 children admitted in paediatric department and gastroenterology unit of medicine department with confirmed acute viral hepatitis from June 2016 to July 2018 at tertiary health care teaching hospital of north India were included. The patients were divided in 3 age groups; 1-5, 6-10 and 11-18 years. Clinical features, laboratory parameters, ultrasound findings were compared in three age groups. Results: Out of 88 cases 48 were boys and 40 girls. In the present study hepatitis A was the most common (85.2%) etiology. Jaundice (90.9%) is the most common symptoms followed by dark colored urine (86.3%), loss of appetite (83.3%) and fever (68.2%) reported in this study. Icterus (90%) is the most common sign reported followed by hepatomegaly (86%). Out of 88 cases 4 cases died. Out of 4 deaths, 2 cases of hepatitis A and 2 cases positive for Hepatitis B. The cause of death was hepatic encephalopathy in both the cases. Conclusions: Majority of cases in children were hepatitis A cases. Most of the cases were aged above 5 years with slight male predominance. Those cases with elevated liver enzymes (SGOT >5000) and those with PT INR >3.5 at admission has higher mortality.